Preparedness for the future pandemic: understanding the impacts of risk perception in public health emergencies - Aung, Khin Thandar; Abdul Razak, Rafiza; Mohd Nazry, Nor Nazrina (Asia Pacific Higher Learning Sdn Bhd., 2023)
This paper emphasizes the significance of risk perception in public health emergencies and its impact on preparedness for future pandemics. It investigates the influence of risk perception on individual and community behaviors during previous outbreaks, highlighting factors that shape people's perceptions of risk. Effective risk communication strategies are identified as crucial in shaping risk perception and promoting proactive preparedness measures. It is believed that tailored interventions addressing psychological, cultural, and socioeconomic factors are required to address the diverse risk perceptions among different populations. Understanding risk perception dynamics enables policymakers and public health practitioners to develop targeted strategies for enhanced preparedness and response efforts in future pandemics, ultimately mitigating the impact on public health and society.